1998
DOI: 10.1289/ehp.106-1533252
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of the estrogenic effects of pesticides and environmental chemicals by curcumin and isoflavonoids.

Abstract: Many environmental chemicals and pesticides have been found to be estrogenic and have been shown to stimulate the growth of estrogen receptor-positive (ER-positive) human breast cancer cells. Since it is difficult to avoid human exposure to environmental estrogens, a potentially important area of research is the development of dietary strategies to prevent the stimulated growth of breast tumors by environmental estrogens. In this context, the inhibitory action of curcumin and a combination of curcumin and isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 27 publications
1
30
0
2
Order By: Relevance
“…Mol Cancer Ther 2007;6 (11 increased uPA expression may diminish cell-cell adhesion and attachment to the extracellular matrix, which would result in increased cell motility. Hence, cell motility was investigated using the wound assay.…”
Section: Molecular Cancer Therapeutics 3075mentioning
confidence: 99%
“…Mol Cancer Ther 2007;6 (11 increased uPA expression may diminish cell-cell adhesion and attachment to the extracellular matrix, which would result in increased cell motility. Hence, cell motility was investigated using the wound assay.…”
Section: Molecular Cancer Therapeutics 3075mentioning
confidence: 99%
“…DISCUSSION Curcumin has been shown to have chemopreventive effects on breast cancer. 20,21 Recently, Inano et al have reported that curcumin has a potent preventive activity during the DES-dependent promotion stage of radiation-induced mammary tumorigenesis. 20 In our study, we provide evidence that curcumin exerts multiple different suppressive effects on human breast carcinoma cells in vitro.…”
Section: Curcumin's Modulation Of Angiogenesis Factor Expressionmentioning
confidence: 99%
“…Studies have shown that phytoestrogens may prevent cancers, act as antioxidants, scavenge free radicals, lower serum cholesterol, have antiestrogenic and antiproliferative effects [15][16][17][18][19]. Isoflavones can act as weak estrogens on estrogen receptors, strong enough to promote bone formation and reduce risk for cardiovascular disease, but not potent enough to induce hormone-related cancers [20,21]. Therefore, the phytoestrogens containing high levels of isoflavones may be good candidates for alternatives of HRT.…”
Section: Introductionmentioning
confidence: 99%